High sensitivity C-reactive protein level in various manifestations of tuberculosis in children - Radita Kusumaningrum; Moh Syarofil Anam; Dwi Wastoro Dadiyanto; Maria Mexitalia; Magdalena Sidhartani (Paediatrica Indonesiana, 2021)
Background Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Of all TB patients, 40-50% are children. C-reactive protein (CRP) is produced during the inflammation process and is an indicator of active TB disease. High sensitivity CRP (hs-CRP) test has higher accuracy and sensitivity to detect CRP at lower levels. Objective To compare hs-CRP in children with TB infection, pulmonary TB, and extra-pulmonary TB. Methods This cross-sectional study of children with tuberculosis was conducted at Dr. Kariadi Hospital and the Semarang Community Health Center, Semarang, Central Java, from January 2020–February 2021. Inclusion criteria were patients aged 1–18 years with suspected TB (contact with adult TB patient or clinically suspected to have TB). Results From 95 study subjects, 19 had TB infection, 51 had pulmonary TB, and 25 had extra-pulmonary TB. There was a significant increase in hs-CRP level based on prolonged fever (P<0.001), enlarged lymph glands (P=0.004), joint swelling (P=0.006), low WHZ or BMI for age (P=0.048), positive bacteriological evidence (P<0.001), and negative/not done tuberculin skin test (P=0.001). There was a significant difference of hs-CRP level based on TB status, with the highest hs-CRP level in extra-pulmonary TB [14.3 mg/l (0.16–321.5)], followed by pulmonary TB [0.8 mg/l (0.3–129.1)], and TB infection [0.7 mg/l (0.3–20.2)]. The highest hs-CRP level for extra-pulmonary TB was found in abdominal TB [84.5 mg/l (0.6–321.5)]. Conclusion Children with extra-pulmonary TB have significantly higher hs-CRP than children with TB infection or pulmonary TB.